2017
DOI: 10.11648/j.jctr.20170502.11
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Storage at Temperature (4C) on Complete Blood Count Parameters

Abstract: Abstract:Background: Complete blood counts are done to monitor overall health, to screen for some diseases, to confirm a diagnosis of some medical conditions, to monitor a medical condition, and to monitor changes in the body caused by medical treatments. Most blood counts today include a CBC count and leukocyte differential count (LDC) (that is, not just the total WBC count but also the count of each WBC type, such as neutrophils, eosinophils, basophils, monocytes, and lymphocytes). More sophisticated modern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The same study by Daves et al (2015) showed significant differences in the number of erythrocytes in human blood samples stored for 6 hours in K2EDTA at 4°C. Different study results were reported by Ali (2017); the number of erythrocytes in human blood samples stored for 72 hours in K3EDTA at 4°C did not show significant differences. The results of another study reported that storing human blood samples for 8 hours in K3EDTA at room temperature did not show a significant difference in the number of erythrocytes (Putri et al, 2019).…”
Section: Total Erythrocyte Countmentioning
confidence: 54%
See 1 more Smart Citation
“…The same study by Daves et al (2015) showed significant differences in the number of erythrocytes in human blood samples stored for 6 hours in K2EDTA at 4°C. Different study results were reported by Ali (2017); the number of erythrocytes in human blood samples stored for 72 hours in K3EDTA at 4°C did not show significant differences. The results of another study reported that storing human blood samples for 8 hours in K3EDTA at room temperature did not show a significant difference in the number of erythrocytes (Putri et al, 2019).…”
Section: Total Erythrocyte Countmentioning
confidence: 54%
“…Putri et al (2019) reported a similar study's results that the hemoglobin levels of human blood samples stored for 8 hours in K3EDTA anticoagulant did not show significant differences. The results of the study by Ali (2017) reported that hemoglobin levels in fresh blood samples with K3EDTA anticoagulant at 24, 48, and 72 hours of storage at 4°C did not show significant differences.…”
Section: Hemoglobin Concentrationmentioning
confidence: 95%
“…2 Complete hemogram is also necessary for patients who requires blood transfusion to estimate the quantity of blood to be transfused. 3 The capability of sample to retain the initial value of a measured quantity for defined period within specific limits when stored under defined condition is termed as sample stability. 4 This sample stability is essential to maintain accuracy & reliability of final results in case of delayed evaluation of blood samples.…”
Section: Introductionmentioning
confidence: 99%